Observation of the embryonic development in Pseudoplatystoma coruscans (Siluriformes: Pimelodidae) under light and scanning electron microscopy - Marques, Camila [UNESP]; Okada Nakaghi, Laura Satiko [UNESP]; Faustino, Francine [UNESP]; Ganeco, Luciana Nakaghi [UNESP]; Senhorini, Jose Augusto (Cambridge University Press, 2008)
Pseudoplatystoma coruscans is a very popular species for tropical fish culture as it has boneless meat of delicate taste and firm texture. Few studies on fish reproductive biology refer to the morphological features of eggs. The goal, therefore, of this present work was to perform a structural and ultrastructural analysis of fertilization and embryonic development in R coruscans. The incubation period, from fertilization to hatching, lasts 13 h at 28/29 degrees C and 18 h at 27 degrees C. The oocytes had a mean diameter of 0.95 mm and hatched larvae were 2.55 mm in diameter. Analysing their development, we observed round, yellow oocytes that bore a double chorion membrane and a single micropyle. At 10 s after fertilization, several spermatozoa were detected attached to the oocyte surface. After I min of development, a fertilization cone that obstructed the micropyle could be observed. Segmentation started between 20 and 30 min after fertilization, when the egg cell was then formed. The first cleavage occurred between 30 and 45 min after fertilization, prior to reaching the morula stage (75 and 90 min after fertilization). The epiboly movement started at 120 and 180 min after fertilization and ended at 360 and 480 min after fertilization. Differentiation between cephalic and caudal region was detected after 420 and 600 min after fertilization and larvae hatched between 780 and 1080 min after fertilization. Seven main embryonic development stages were identified: egg cell, cleavage, morula, blastula, gastrula, segmentation with differentiation between cephalic and caudal regions, and hatching.
Keywords: Eggs; Embryology; Morphology; Pseudoplatystoma corruscans; SEM